2020
DOI: 10.7150/jca.36438
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of CYP4A11 expression in renal cell carcinoma: diagnostic and prognostic implications

Abstract: Background: Cytochrome P-450 4A11 (CYP4A11) and peroxisome proliferator-activated receptor-α (PPARα) are expressed at high levels in renal proximal tubules, and upregulation of CYP4A11 protein levels is known to be influenced by PPAR agonists. The goal of this study was to evaluate the clinicopathological role of CYP4A11 expression in renal cell carcinoma (RCC). Methods: We performed immunohistochemical analysis of CYP4A11, CYP4A22 and PPARα and correlated the results with the clinicopathological features of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…In this study, based on our cohort of 52 paired ccRCC tumor tissues and matched adjacent non-tumor tissues, we showed the overexpression of miR-21 in ccRCC as well as an inverse correlation between miR-21 and PPAR-α expression. Consistent with Kim et al [33], we also showed that the PPAR-α protein level was barely detectable in most ccRCC clinical samples, suggesting that miR-21 may influence PPAR-α expression and consequently its activity. As PPAR-α is a bona fide target of miR-21, we performed a series of experiments aiming to better characterize the regulatory mechanism shared by miR-21, PPAR-α, and lipid metabolism in ccRCC.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, based on our cohort of 52 paired ccRCC tumor tissues and matched adjacent non-tumor tissues, we showed the overexpression of miR-21 in ccRCC as well as an inverse correlation between miR-21 and PPAR-α expression. Consistent with Kim et al [33], we also showed that the PPAR-α protein level was barely detectable in most ccRCC clinical samples, suggesting that miR-21 may influence PPAR-α expression and consequently its activity. As PPAR-α is a bona fide target of miR-21, we performed a series of experiments aiming to better characterize the regulatory mechanism shared by miR-21, PPAR-α, and lipid metabolism in ccRCC.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, with the development of molecular biology technology and bioinformatics, new biomarkers have the potential to be used as prognostic factors for different types of cancer, including pRCC. For instance, some studies have found that CYP4A11 expression is a potential poor prognostic factor for RCC [8], while others have detected long noncoding RNAs that might serve as prognostic biomarkers for pRCC [9], and some alternative splicing events also correlate with pRCC prognosis [10]. Therefore, finding new molecular markers to predict the clinical outcome of pRCC is of great significance for understanding pRCC's molecular pathological characteristics, prognosis, and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…CYP4A11, a member of CYP4 family, is involved in fatty acid metabolism. It is decreased in tumor tissues such as hepatocellular carcinoma, 21 renal cell carcinoma, 22 and lung cancer 5 . PGM2 is an alpha‐phosphate glucose mutase.…”
Section: Discussionmentioning
confidence: 99%